Spinning the Industrial Revolution - Humphries, J; Schneider, B (University of Oxford, 2016)
The prevailing explanation for why the Industrial Revolution occurred first in Britain is Robert Allen's (2009) 'high?wage economy' view, which claims that the high cost of labour relative to capital and fuel incentivized innovation and the adoption of new techniques. This paper presents new empirical evidence on hand spinning before the Industrial Revolution and demonstrates that there was no such 'high?wage economy' in spinning, a leading sector of industrialization. We quantify the working lives of frequently ignored female and child spinners who were crucial to the British textile industry in the Early Modern period with evidence of productivity and wages from the late sixteenth to the early nineteenth century. Our results show that spinning was a widespread, low?wage, low?productivity employment, in line with the Humphries (2013) view of the motivations for the factory system.